An assembly perspective of entrepreneurial projects: social networks in action - Obstfeld, D; Ventresca, M; Fisher, G (Wiley, 2020)
We introduce a process model of microsocial network dynamics that incorporates an assembly perspective of entrepreneurial action in early-stage projects. The model comprises four conceptual elements: (1) an initial entrepreneurial projection or goal, which motivates and guides network-based action, and evolves as it is the venture unfolds; (2) knowledge articulation to make the entrepreneurial projection relevant to stakeholders; (3) combinatorial action, which entails joining people and resources in new combinations and that may reshape the project; and (4) network expansion by which stakeholder relationships develop and generate distributed momentum. This approach integrates and extends foundational theoretical perspectives in entrepreneurship––bricolage, effectuation, and opportunity creation, drawing on recent developments in social network process theory to inform the model.